The Cambridge Companion to Medievalism - D'Arcens, Louise (Cambridge companions to culture)
"Medievalism - the creative interpretation or recreation of the European Middle Ages - has had a major presence in the cultural memory of the modern West, and has grown in scale to become a global phenomenon. Countless examples across aesthetic, material and political domains reveal that the medieval period has long provided a fund of images and ideas that have been vital to defining 'the modern'. Bringing together local, national and global examples and tracing medievalism's unpredictable course from early modern poetry to contemporary digital culture, this authoritative Companion offers a panoramic view of the historical, aesthetic, ideological and conceptual dimensions of this phenomenon. It showcases a range of critical positions and approaches to discussing medievalism, from more 'traditional' historicist and close-reading practices through to theoretically engaged methods. It also acquaints readers with key terms and provides them with a sophisticated conceptual vocabulary for discussing the medieval afterlife in the modern"--